Proposed code provisions for slab span thickness limitations including early-age construction loads and time-dependent effects. - Ofosu-Asamoah, Kwabena. (University of Ottawa (Canada), 1993)
A typical construction procedure for a multi-storey reinforced concrete building involves supporting newly cast slabs on a number of previously cast floors through a reshore system. The loads transferred by the forms to the previously cast partially cured supporting slabs may appreciably exceed the design capacity. A further complication is that large early-age construction loads applied to immature slabs will cause large immediate deflections and extensive flexural cracking. The large ratio of applied stress to developed strength, coupled with the low elastic moduli of the immature slabs, will cause significant creep, mostly non-recoverable, resulting in large longterm deflections. Shrinkage, though a non-stress originated concrete deformation phenomena, also affects concrete deformation and needs to be accounted for in calculations to predict longterm deflections. Most cases of deflection damage occur as a result of exceeding the permissible deflection of slabs supporting non-structural elements. This creates serviceability problems such as cracked partitions, jamming of doors and windows, and an uneven placement of furniture. In most cases, the visual impact of cracks and sagging floors may cause concern for safety of the structure even if the structure has adequate strength. Problems related to excessive slab deflection constitutes a serviceability limit state. Current deflection control provisions of the ACI and CSA codes do not address the sensitivity of slab deflections to early-age construction loading and schedule. The present study develops a more realistic span-thickness criterion which includes the effect of early-age construction loads, concrete strength and panel aspect ratio. Undesirable slab deflections can be reduced by appropriately chosen camber in the formwork. The concept is to use a prescribed camber to offset the immediate deflections. An equation is recommended for the estimation of the amount of camber needed for any given span.
Keywords: Engineering, Civil.